Analisis Dampak Transformasi Digital terhadap Mutu Layanan Pendidikan dan Mutu Pembelajaran di MTs YAPDI Medan - Lutfiah Malaya Alfa; Makmur Syukri (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Digital transformation has become a strategic agenda in the management of educational institutions, including madrasas, as an effort to improve the quality of educational services and learning. However, the implementation of digital transformation in Islamic education still faces various challenges, both in terms of human resource readiness and institutional system support. This study aims to analyze the implementation of digital transformation and its impact on the quality of educational services and learning at MTs YAPDI Medan. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews with the madrasah principal, teachers, and education personnel, supported by observation and documentation studies. Data analysis was conducted using the interactive model of Miles and Huberman through the stages of data reduction, data presentation, and drawing conclusions. The results show that digital transformation at MTs YAPDI Medan has been implemented effectively in aspects of educational administration services through the use of digital systems such as EMIS, RKM, EDM, and digital payment services. This implementation has been proven to increase the efficiency, neatness, transparency, and reliability of administrative services. However, the impact of digital transformation on learning quality has not been optimal. The use of technology in learning remains limited, unequally distributed among teachers, and pedagogically unintegrated into learning planning, implementation, and evaluation. The conclusion of this study confirms that digital transformation in madrasas has had a greater impact on improving the quality of educational services than on the quality of learning. Therefore, strengthening digital transformation in the future needs to be directed at developing teachers' digital pedagogical competencies and providing ongoing system support so that technology truly contributes to improving the quality of learning.